Efisiensi Teknis Usaha Budidaya Pembesaran Ikan Lele di Kolam (Studi Kasus di Kabupaten Tulung Agung, Propinsi Jawa Timur) - Tajerin Tajerin (Economic Journal of Emerging Markets, 2007)
Fish culture technical efficiency level is signal of fish farmer’s achievement concerning his managerial ability in managing important factors of production which affect the productivity of his business. The research aim to evaluated level of technical efficiency of catfish growth out culture and factors affecting. The research was conducted in Tulung Agung regency, East Java Province during September to December in 2005. The respondent of catfish farmer was selected by stratified random sampling method. The result of research showed that average of technical efficiency level received by catfish farmers in ponds was classified in middle – high category and relatively smooth. The main factor affecting the technical efficiency rate is catfish culture related family income share from the total income. Other proven conducive factors are catfish culture training, total per capita income, recommended technological adoption, participatory in catfish farming group and catfish culture farmer’s age. Since the technical efficiency level achieved is no where close to the frontier, therefore the development policy for catfish culture should be on spread group approach with application the culture technology are really imperative and innovate.  Keywords: technical efficiency, growth out, catfish, pond